The Ttraining Needs of Teaching Members at the Algerian University and their Role in Improving Distance Teaching Skills A Field Study of a Sample of Professors from Setif 02 University (El-Wahat Journal for Research and Studies, 2026)
This study addresses the issue of teaching skills of university faculty members in Setif 02 University in light of the changes that have occurred in the reality of education in institutes and institutions of higher education. We followed a set of methodological steps, selecting the descriptive method based on the survey approach by sample, where a representative sample of the teaching staff at the University of Setif 02 was chosen while the human scope consists of selecting a sample from the teaching staff comprising 50 individuals. The aim was to determine the attitudes and opinions of this sample toward the issue of distance training needs and their role in improving teaching skills.  We reached a set of results, the most important of which are: that the attitudes and opinions of faculty members toward the importance and objectives of the training process in Algerian universities the weakness of the training process outputs for distance teaching, and the necessity of activating training courses for distance education. As for the nature of the training needs that Setif 2 University should rely on, respondents indicated that the need for training in the use of modern pedagogical tools is urgent and necessary.
Keywords: Role, Training needs, Teaching skills, Teaching staff.